2020
DOI: 10.3389/fimmu.2020.611004
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Subsets as Severity-Associated Signatures in COVID-19 Patients

Abstract: BackgroundSARS-CoV-2 infection represents a global health problem that has affected millions of people. The fine host immune response and its association with the disease course have not yet been fully elucidated. Consequently, we analyze circulating B cell subsets and their possible relationship with COVID-19 features and severity.MethodsUsing a multiparametric flow cytometric approach, we determined B cell subsets frequencies from 52 COVID-19 patients, grouped them by hierarchical cluster analysis, and corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
119
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 56 publications
25
119
1
1
Order By: Relevance
“…Moreover, in these previously infected CVID patients, IgG response was boosted by the subsequent immunization. Interestingly, in all CVID patients, vaccination induced Trimeric Spike-specific B-cells inside the ATM and PB population, with low affinity for Trimeric Spike, possibly suggesting that the B-cell responses occurred mostly at extra-follicular sites [32] as recently demonstrated [33]. In line with this hypothesis, RBD+ B-cells were undetectable in CVID patients, whereas they represent 20% of the highly specific anti-Trimeric Spike response in HD (unpublished data) able to develop and successfully terminate the germinal center reaction [34].…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, in these previously infected CVID patients, IgG response was boosted by the subsequent immunization. Interestingly, in all CVID patients, vaccination induced Trimeric Spike-specific B-cells inside the ATM and PB population, with low affinity for Trimeric Spike, possibly suggesting that the B-cell responses occurred mostly at extra-follicular sites [32] as recently demonstrated [33]. In line with this hypothesis, RBD+ B-cells were undetectable in CVID patients, whereas they represent 20% of the highly specific anti-Trimeric Spike response in HD (unpublished data) able to develop and successfully terminate the germinal center reaction [34].…”
Section: Discussionsupporting
confidence: 52%
“…DN B cells are suggested to be the precursors of antibody secreting cells in SLE patients and to develop outside the germinal center (36,37). While DN B cells can be detected in healthy individuals, they expand in patients with SLE (38), rheumatoid arthritis (39), nonsmall cell lung cancer (40), and COVID-19 (41). Furthermore, it has been reported that DN B cells increased in pediatric acute renal allograft rejection recipients who received steroid pulsing, compared to patients with stable graft function (42).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates a critical role of immune cells, which are primarily hematopoietic, in the development of severe COVID-19 [16][17][18][19] . To profile the cell-cell interactions underlying severe COVID-19 from a genetic perspective, we constructed a cell correlation matrix based on the overlap of RefMap genes between cell types ( Fig.…”
Section: Refmap Analysis Of Common Variants Uncovers Cell-type-specific Genetic Basis Of Covid-19 Severitymentioning
confidence: 98%
“…Profiles of the immune response associated with severe COVID-19 have produced a number of conflicting observations. These studies have variously linked COVID-19 severity to CD8 T cells 16 , CD19 B cells 17 , eosinophils 18 , and myeloid cells 19 . Single-cell omic profiling has demonstrated the differential function of various immune cell types in severe disease as opposed to mild disease or non-infected condition [20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%